Technology acceptance and use among nursing staff in Latin American hospitals: A mixed methods study - Juan Manuel Aranda; María Elisa Moreno-Fergusson; William Javier Guerrero; Beatriz Sanchez Herrera; María Alejandra Galiano; Maryory Guevara; Ingrid Xiomara Bustos; Francisca Muñóz (International Journal of Nursing Studies Advances)
Background: Digital health technologies can improve health outcomes and the efficiency of healthcare delivery when used appropriately. Nevertheless, the human-computer interaction is a concern in compassionate patient care and nurses' professional well-being. Objective: To analyze the degree of technological acceptance and use within nurses in two Latin American university hospitals. Design: A mixed methods study design. Setting(s): Two Latin American university hospitals, one in Chile and the other in Colombia. Participants: A total of 53 nurses participated in the study. In phase 1, 31 nurses took part, with 15 from a Chilean hospital and 16 from a Colombian hospital. In phase 2, 22 nurses participated, with 14 in Chile and 8 in Colombia. Methods: : A mixed methods sequential study was conducted in inpatient services. It was developed in three phases. First, a quantitative one with a call to all nurses in two institutions, in Chile and Colombia. A scale of the unified theory of acceptance and use of technology, adapted to nursing in Spanish, was employed following expert validation both facial and content aspects. Second, a qualitative one with four focus groups with service coordinator nurses and in-depth interviews with nursing managers or supervisors. These sessions were recorded and transcribed verbatim. Quantitative data were analyzed using descriptive statistics and hypothesis testing for mean differences, while qualitative data underwent content analysis. Finally in the third phase, both qualitative and quantitative data were integrated to establish the acceptability and use of the technology. Results: Quantitative analysis revealed a statistically significant positive correlation between behavioural intention to use the system and facilitating conditions (r(31)=0.50, p<.01). Also, there is a positive correlation between behavioural intention to use the system and effort expectancy in Chile (r(13)=0.60, p<.05). Additionally, a statistically significant difference (p<.05) exists between the two institutions regarding social influence and facilitating conditions. Qualitative data confirmed these findings. Integration made it possible to specify the factors such as the performance expectancy, facilitating conditions, and anxiety determine the acceptability and use of technology by nurses in the studied institutions. Conclusions: The degree of technological adoption among nursing staff in two Latin American university hospitals is currently 3.7±0.4 (scale from 1 to 5). Understanding the aspects that affect the acceptance and use of technologies paves the way for achieving their best use in support of nursing care. Registration: ING-256-2020, January 16, 2023. Tweetable abstract: Nurses in Latin American show mixed tech acceptance. Understanding barriers is crucial for better care delivery #DigitalHealth #NurseTech